View of the main entrance and side entrance to the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
View of the west-facing main entrance and side entrance to the Bhandasar Temple. The entrances have semi-circular coloured glass windows, one of the essential influences of the British era period on the paintings in the temples. The eighteen and sixteen side bands of the ceiling were painted based on various themes.